The Effect of Work Engagement, Work Environment, Work Motivation On Employee Performance Mediated by Job Satisfaction at KPP Pratama Gresik - Ispon Asep Yurano; I Made Bayu Dirgantara; Shine Pintor Siolemba (Lead Journal of Economy and Administration, 2024)
The study aims to examine the effect of work engagement, work environment and work motivation on employee performance mediated by job satisfaction at KPP Pratama Gresik. The sample in this study consisted of 108 employees of KPP Pratama Gresik. The main data source in this study was a questionnaire. The data processing application in this study uses smartPLS 3.0. The results showed that work engagement affects employee job satisfaction at KPP Pratama Gresik, work environment has no effect on employee job satisfaction at KPP Pratama Gresik, work motivation affects employee job satisfaction at KPP Pratama Gresik, job satisfaction affects employee performance at KPP Pratama Gresik, work engagement affects employee performance at KPP Pratama Gresik, Work environment has no effect on employee performance at KPP Pratama Gresik, Work motivation affects employee performance at KPP Pratama Gresik, Job satisfaction is not able to mediate the effect of work engagement and work environment on employee performance at KPP Pratama Gresik, and finally Job satisfaction is able to mediate the effect of work motivation on employee performance at KPP Pratama Gresik.